Analisis Kelayakan Teknis Dan Finansial Usaha Tani Jeruk Lemon (Citrus limon) Di Kecamatan Cihaurbeuti, Kabupaten Ciamis - Miftah Farid; Hendar Nuryaman; Nurul Risti Mutiarasari (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2025)
Lemons (Citrus limon) have considerable potential for further development in Indonesia, although the country still relies on imports to meet its domestic demand. This study aims to analyse the feasibility of lemon farming from technical and financial perspectives, as well as its sensitivity to fluctuations in input and output prices. The research employed a descriptive method using a case study approach on a lemon farmer in Sukamulya Village, Cihaurbeuti District, Ciamis Regency. Technical feasibility was assessed using the Crop Management guidelines issued by APNI Kheti. Financial feasibility was evaluated using four investment criteria, namely Net Present Value (NPV), Net Benefit–Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP), complemented by sensitivity analysis. The results indicate that, from a technical perspective, lemon farming achieved a conformity level of 61.29% with the Crop Management standards issued by APNI Kheti. Financial feasibility analysis shows a positive NPV of IDR 3,733,653,738, a Net B/C of 4.85, an IRR of 22.80%, and a payback period of 5 years and 8 months. Sensitivity analysis reveals that a 25% increase in labour costs and a 40% decrease in the selling price of lemons reduce the values of NPV, Net B/C, IRR, and PP; however, these indicators remain within acceptable limits, indicating that lemon farming remains financially feasible for further development.